Neoproterozoic‐Early Paleozoic Peri‐Pacific Accretionary Evolution of the Mongolian Collage System: Insights From Geochemical and U‐Pb Zircon Data From the Ordovician Sedimentary Wedge in the Mongolian Altai. Issue 11 (3rd November 2017) - Jiang, Y. D.; Schulmann, K.; Kröner, A.; Sun, M.; Lexa, O.; Janoušek, V.; Buriánek, D.; Yuan, C.; Hanžl, P.
Abstract: Neoproterozoic to early Paleozoic accretionary processes of the Central Asian Orogenic Belt have been evaluated so far mainly using the geology of ophiolites and/or magmatic arcs. Thus, the knowledge of the nature and evolution of associated sedimentary prisms remains fragmentary. We carried out an integrated geological, geochemical, and zircon U‐Pb geochronological study on a giant Ordovician metasedimentary succession of the Mongolian Altai Mountains. This succession is characterized by dominant terrigenous components mixed with volcanogenic material. It is chemically immature, compositionally analogous to graywacke, and marked by significant input of felsic to intermediate arc components, pointing to an active continental margin depositional setting. Detrital zircon U‐Pb ages suggest a source dominated by products of early Paleozoic magmatism prevailing during the Cambrian‐Ordovician and culminating at circa 500 Ma. We propose that the Ordovician succession forms an "Altai sedimentary wedge, " the evolution of which can be linked to the geodynamics of the margins of the Mongolian Precambrian Zavhan‐Baydrag blocks. This involved subduction reversal from southward subduction of a passive continental margin (Early Cambrian) to the development of the "Ikh‐Mongol Magmatic Arc System" and the giant Altai sedimentary wedge above a north dipping subduction zone (Late Cambrian‐Ordovician). Such a dynamic process resembles the tectonic evolution of the peri‐Pacific accretionary Terra Australis Orogen. A new model reconciling the Baikalian metamorphic belt along the southern Siberian Craton with peri‐Pacific Altai accretionary systems fringing the Mongolian microcontinents is proposed to explain the Cambro‐Ordovician geodynamic evolution of the Mongolian collage system. Key Points: The Mongolian Altai represents an Ordovician accretionary wedge riming the active margins of the northerly Precambrian blocks Western margins of Mongolian Precambrian blocks switched from an Early Cambrian passive margin to a Late Cambrian‐Ordovician active one The Mongolian collage system and southern Siberia probably evolved from a peri‐Pacific subduction system in Cambro‐Ordovician